2018 European Conference on Optical Communication (ECOC) 2018
DOI: 10.1109/ecoc.2018.8535324
|View full text |Cite
|
Sign up to set email alerts
|

Record Low-Loss 1.3dB/km Data Transmitting Antiresonant Hollow Core Fibre

Abstract: We report fabrication of a Nested Antiresonant Nodeless hollow-core Fibre (NANF) with a minimum loss of 1.3dB/km at 1450nm and a 65nm bandwidth below 1.5dB/km. The 0.5-km long fibre is effectively single moded and is shown capable of data transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…Moreover, theoretical studies have identified a potential low loss (<0.15 dB/km) and a very low chromatic dispersion (CD) over almost the entire transmission window (<2 ps/(nm•km)) [20]. This potential is supported by a recent demonstration of a 0.5 km length HC-ARF with a loss of 1.3 dB/km [22], outperforming the lowest rigorously documented loss in a HC-PBGF (1.7 dB/km) [23]. Arguably the key potential advantage of HC-ARF lies in the potential for very high transmission capacities using wide wavelength range dense wavelength division multiplexing (DWDM) and high-order modulation formats due to the anticipated very high nonlinearity tolerance.…”
mentioning
confidence: 89%
“…Moreover, theoretical studies have identified a potential low loss (<0.15 dB/km) and a very low chromatic dispersion (CD) over almost the entire transmission window (<2 ps/(nm•km)) [20]. This potential is supported by a recent demonstration of a 0.5 km length HC-ARF with a loss of 1.3 dB/km [22], outperforming the lowest rigorously documented loss in a HC-PBGF (1.7 dB/km) [23]. Arguably the key potential advantage of HC-ARF lies in the potential for very high transmission capacities using wide wavelength range dense wavelength division multiplexing (DWDM) and high-order modulation formats due to the anticipated very high nonlinearity tolerance.…”
mentioning
confidence: 89%
“…1b with the experimental modefield image in Fig. 1a [2]. The transverse Poynting vectors, S x (x,y) and S y (x,y), represent the flow of power in the transverse plane, we use these vector fields to draw our streamlines.…”
Section: Visualizing the Transverse Flow Of Powermentioning
confidence: 99%
“…The lowest reported loss in a data-transmitting hollow core fiber is 1.3 dB/km, recently measured in a Nested Antiresonant Nodeless Fiber (NANF) [2]. To reduce the still considerable loss gap to SSMFs and make hollow core fiber technology even more appealing to optical communications, fiber designers need to find structural ways to reduce the NANF's leakage loss, simulations indicate this is their dominant loss mechanism [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such applications are among the important motivations for development of HCFs and data transmission was demonstrated in an air-core PBG fiber already in 2013 [13]. Dramatic improvement in bringing down of attenuation -ultimately to around 1 dB/km -prompted later demonstrations of data transmission in hollow core ARFs in the third telecommunication window, as well [14][15][16]. Mid-infrared guidance in silica fibers is disruptive for gas sensing and spectroscopy applications [5,17].…”
mentioning
confidence: 99%